The Educational Media to Improve Reproductive Health Knowledge among Adolescents: A Systematic Review - Darmayani, Ckristy Diana; Kumboyono, Kumboyono; Nugroho, Fajar Ari; Supriati, Lilik (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
Adolescents often lack knowledge among adolescents regarding reproductive health can lead to many issues related for adolescent. Education to improve adolescents knowledge about reproductive health is important, but the best and most suitable educational media remains varied. This systematic review aims to identify the most effective educational media for improving reproductive health knowledge among adolescents.  A systematic review was conducted following the PRISMA guidelines. Literature was retrieved from PubMed, ScienceDirect, and ProQuest databases, as well as manual searches, using the keywords: adolescence AND reproductive health OR reproduction health AND media of education. Inclusion criteria consisted of original studies published in English from 2018 to 2024, with a focus on educational media interventions related to adolescent reproductive health. A total of 6,295 articles were initially identified, and after applying eligibility criteria, 10 articles were included in the final analysis. The educational media found in the selected studies included printed materials (books and magazines), peer education, policy maker involvement, mobile applications, games, and social media. Among these, peer education was found to be the most effective in increasing reproductive health knowledge among adolescents. Educational media play a crucial role in improving adolescents’ understanding of reproductive health. Selecting the appropriate media, particularly peer-based education, is a key strategy to enhance knowledge and promote healthy reproductive behaviors among adolescents. ABSTRAK Kurangnya pengetahuan remaja mengenai kesehatan reproduksi dapat menimbulkan berbagai masalah pada remaja. Media edukasi untuk meningkatkan pengetahuan remaja tentang kesehatan reproduksi sangatlah penting. Tetapi media edukasi yang terbaik masih begitu beragam. Tinjauan sistematis ini bertujuan untuk mengidentifikasi dan mengevaluasi jenis media edukasi yang paling efektif dalam meningkatkan pengetahuan kesehatan reproduksi pada remaja. Penelitian ini menggunakan metode tinjauan sistematis berdasarkan panduan PRISMA. Literatur diperoleh dari database PubMed, ScienceDirect, dan ProQuest serta pencarian manual dengan kata kunci: Remaja AND Kesehatan Reproduksi OR Kesehatan Reproduksi AND Media Pendidikan. Kriteria inklusi meliputi artikel asli berbahasa Inggris yang diterbitkan antara tahun 2018 hingga 2024, dan membahas intervensi media edukasi terkait kesehatan reproduksi remaja. Dari total 6.295 artikel yang ditemukan, 10 artikel memenuhi kriteria untuk dianalisis lebih lanjut. Media edukasi yang diidentifikasi dalam penelitian meliputi media cetak (buku dan majalah), pendidikan sebaya, keterlibatan pembuat kebijakan, aplikasi digital, permainan, dan media sosial. Di antara semua jenis media, pendidikan sebaya terbukti paling efektif dalam meningkatkan pengetahuan kesehatan reproduksi pada remaja. Media edukasi memiliki peran penting dalam meningkatkan pemahaman remaja terhadap kesehatan reproduksi. Pemilihan media yang tepat, terutama pendekatan pendidikan sebaya, menjadi strategi utama untuk meningkatkan pengetahuan dan membentuk perilaku reproduktif yang sehat pada remaja.